2017
DOI: 10.1016/j.cell.2017.07.038
|View full text |Cite
|
Sign up to set email alerts
|

DNA Cross-Bridging Shapes a Single Nucleus from a Set of Mitotic Chromosomes

Abstract: SummaryEukaryotic cells store their chromosomes in a single nucleus. This is important to maintain genomic integrity, as chromosomes packaged into separate nuclei (micronuclei) are prone to massive DNA damage. During mitosis, higher eukaryotes disassemble their nucleus and release individualized chromosomes for segregation. How numerous chromosomes subsequently reform a single nucleus has remained unclear. Using image-based screening of human cells, we identified barrier-to-autointegration factor (BAF) as a ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
256
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(265 citation statements)
references
References 90 publications
(143 reference statements)
7
256
2
Order By: Relevance
“…It is plausible that transient changes in NE organization at NE rupture sites may signal or support membrane insertion (De Vos et al, 2011;Denais et al, 2016;Raab et al, 2016;Penfield et al, 2018). For instance, BAF crosslinks chromatin at the core region of chromatin that coincides with spindle microtubules (Samwer et al, 2017) and was recently shown to accumulate at rupture sites (Halfmann et al, 2019), providing a possible mechanism to direct membrane incorporation to this region. Identifying how ER sheets are delivered into NE holes in different contexts is an important next step.…”
Section: Resultsmentioning
confidence: 99%
“…It is plausible that transient changes in NE organization at NE rupture sites may signal or support membrane insertion (De Vos et al, 2011;Denais et al, 2016;Raab et al, 2016;Penfield et al, 2018). For instance, BAF crosslinks chromatin at the core region of chromatin that coincides with spindle microtubules (Samwer et al, 2017) and was recently shown to accumulate at rupture sites (Halfmann et al, 2019), providing a possible mechanism to direct membrane incorporation to this region. Identifying how ER sheets are delivered into NE holes in different contexts is an important next step.…”
Section: Resultsmentioning
confidence: 99%
“…BAF is a small 89-aa protein, that forms dimmers, which are able to bind dsDNA, and thus capable of bridging between two strands of DNA, and thereby, to potentially affect DNA condensation (Bradley et al, 2005;Zheng et al, 2000). Alternatively, BAF dimers may bind to inner components of the nuclear membrane, including Lap-2, emerin, MAN1 (LEM) domain proteins, or to lamin A/C or B, as well as to dsDNA, and thus promote the association of dsDNA with the nuclear membrane (Cai et al, 2001;Lee et al, 2001;Mansharamani and Wilson, 2005;Samwer et al, 2017). Proteomic analysis of BAF partners indicated its potential association with additional proteins, including transcription factors, damage-specific DNA binding proteins, and histones (Holaska et al, 2003;Montes de Oca et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, many questions remain to be answered about the mechanisms underlying this cellular 'heartbeat' of life. Writing in Cell, Samwer et al 1 now shed light on the mystery of how chromosomes are packaged together in the same nucleus, an outcome known to help protect the integrity of the genome.…”
Section: T E J a S D Hmentioning
confidence: 99%
“…On the more applied side, they might even help chemists to create low-cost fertilizers and organic batteries (see go.nature.com/2jvwchw). In the long run, they could revolutionize our ability to design materials and drugs 1 . Today, however, quantum simulators are still at an early stage of development.…”
Section: Large Quantum Systems Tamedmentioning
confidence: 99%
See 1 more Smart Citation